New qualitative research methodologies in management. Issue 4 (13th May 2014) - Simone Guercini, Professor; Guercini, Simone
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to deliver an introduction to the Special Issue on new qualitative research methodologies in management. Design/methodology/approach – The reasons of interest for the object of this Special Issue are explained through the discussion of a selected literature. Technological and sociological changes are considered as a source of new problem and new opportunities for management and management research. The traditional methods are put under strain by these changes and epistemological implications are considered. Findings – New qualitative methodologies analyzed in the Special Issue are characterized by drivers including hybridization with others methods, both qualitative and quantitative. New methods can contribute to reduce distance between researcher's and practitioner's context. Originality/value – A frame to analyze the new qualitative management research through the papers published in the Special Issue.